Respiratory infections in very low gestational age infants: a population-based cohort study in Estonia - Liis Toome; Silvi Plado; Inge Ringmets; Mari-Anne Vals; Heili Varendi; Irja Lutsar (Hygeia Press di Corridori Marinella, 2014)
Background: There is little comparative information available on the occurrence of respiratory infections (RI) in infants with different degrees of maturity at birth. We aimed to determine the rate and characteristics of RI during the first two years of life in very low gestational age (VLGA) infants compared with the control cohort of full-term (FT) infants and to identify the risk factors for unfavourable outcomes of RI. Methods: The study was a part of a population-based prospective cohort study of VLGA infants born at 22-31 gestational weeks in 2007 in Estonia. At the corrected age of 2 years, surviving 155 VLGA infants were compared with their individually matched FT controls. Perinatal variables were recorded prospectively whereas episodes and characteristics of RI were assessed retrospectively by parental interviews. A logistic regression model was used to test risk factors for unfavourable outcomes (wheezing, recurrent wheezing, and hospitalisation) of RI. Results: The frequency of RI was similar in VLGA and FT infants. However, wheezing as well as recurrent wheezing due to RI was more frequent in VLGA than in FT infants, 34% vs. 21% (OR: 1.9; 95% CI: 1.1-3.2) and 14% vs. 5% (OR: 3.3; 95% CI: 1.4-7.1), respectively. During RI, VLGA infants also needed more hospitalisations (33% vs. 18%; OR: 2.3; 95% CI: 1.3-3.9). There was no significant difference between VLGA infants without bronchopulmonary dysplasia (BPD) compared with FT infants in wheezing and recurrent wheezing. BPD was the main risk factor for all unfavourable outcomes of RI. Conclusions: The frequency of RI in VLGA and FT infants is similar but BPD is more likely than prematurity in itself to predispose VLGA infants to a more severe clinical course of RI.